1989
DOI: 10.1093/bja/63.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Ephedrine During Spinal Anaesthesia: Double-Blind Study in Patients in Asa Groups I–iii

Abstract: Forty-eight patients scheduled to undergo spinal anaesthesia were allocated to three groups of 16 each according to ASA classification I-II-III. Each patient received a fluid load of 7 ml kg-1 and either ephedrine 12.5 mg i.v. and 37.5 mg i.m., or placebo. Twelve patients in the placebo groups developed a maximal decrease in mean arterial pressure exceeding 20%. Five of these (one in ASA II and four in ASA III) developed a decrease exceeding 33% and required treatment. In ASA risk group III, all patients in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 6 publications
0
41
0
Order By: Relevance
“…However, for the elderly patient, i.e. over the age of 60 years, very few articles have been published on the subject in the last 25 years [4, [6][7][8][9][10]. However, since 1992 a series of detailed haemodynamic studies have been reported [ 5 , [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for the elderly patient, i.e. over the age of 60 years, very few articles have been published on the subject in the last 25 years [4, [6][7][8][9][10]. However, since 1992 a series of detailed haemodynamic studies have been reported [ 5 , [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Hemmingsen et a/. [6] [lo] used ephedrine 0.6 mg.kg-I intramuscularly. Phenylephrine 100 p g intravenously every 5min has also been used successfully [9].…”
Section: Background To Treating Hypotensionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Ephedrine, which acts directly at both α and β receptors and indirectly by releasing endogenous norepinephrine, has been used for many years to counteract hypotension and bradycardia in spinal and epidural anesthesia. 6 Gamlin et al 14 studied the hemodynamic effects of propofol in combination with ephedrine. They concluded that addition of ephedrine to propofol appeared to be an effective method of obtunding the hypotensive response to propofol at all doses used in this study.…”
Section: Probable Mechanisms Of Pain On Injection Of Propofolmentioning
confidence: 99%
“…5 It has been used for many years to counteract hypotension and bradycardia in spinal and epidural anesthesia. 6 Ephedrine acts directly at both alpha-and beta-adrenoceptors and indirectly by releasing RIA endogenous norepinephrine. 5 However, recent evidences indicate that ephedrine may reduce the pain of propofol injection and also counteract the hypotension associated with propofol anesthesia.…”
Section: Introductionmentioning
confidence: 99%